Pengaruh Fee Audit, Spesialisasi Auditor, dan Workload terhadap Kualitas Audit: Studi Empiris pada Perusahaan Sektor Keuangan yang Terdaftar di Bursa Efek Indonesia Periode 2022-2024 - Fitri, Novita Sabilia; Pebriyani, Dewi (Jurnal Eksplorasi Akuntansi, 2025)
This research aimed to examine the effect of audit fee, auditor specialization, and workload on audit quality. The population in this research includes all financial sector companies listed on the Indonesia Stock Exchange in the period 2022–2024. The sampling technique used was purposive sampling. Audit quality was proxied by discretionary accruals. The total sample consisted of selected financial companies that met the criteria. The analysis method used in this research was multiple linear regression. The results showed that audit fee had a negative effect on audit quality. Auditor specialization had no significant effect on audit quality. Workload also had no significant effect on audit quality in financial sector companies listed on the Indonesia Stock Exchange in the period 2022–2024.